Activity and safety of apatinib monotherapy or apatinib combined with chemotherapy for patients with metastatic or unresectable osteosarcoma over the age of 40 years: A retrospective analysis - Gong, Taojun; Huang, Qi; Tang, Fan; Wang, Yitian; Li, Zhuangzhuang; Luo, Yi; Min, Li; Zhou, Yong; Tu, Chongqi (Frontiers in Oncology, 2022)
Osteosarcoma commonly developed during childhood and adolescence. Only one-third of osteosarcoma patients have clinically detected over the age of 40 years and survivorship of those patients is quite dismal. Apatinib, a novel multi-target angiogenesis inhibitor, has shown a short-term efficacy in advanced or metastatic osteosarcoma. However, the data of apatinib for the older patients with osteosarcoma are limited. We aim to evaluate the efficacy and safety of apatinib combined with chemotherapy versus apatinib monotherapy in the treatment of patients over 40 years with metastatic or unresectable osteosarcoma.